Determination of Factors Affecting Extraction of Rebaudioside A & Stevioside from Stevia Leaves - Kalaiarasan, Muthusamy; Mimi Sakinah, A. M. (Penerbit Universiti Malaysia Pahang, 2019)
Solid-liquid extraction is a recovery process in which the extracting solvent will recover certain components from a solid material. In this study, three extracting solvents were used which are absolute ethanol, acetone and distilled water. These solvents extracted two sweet components, Rebaudioside A and stevioside from Stevia rebaudiana. These two components can be converted into natural sweetener with zero calorie which does not affect blood glucose level. The objective of this study was to determine the optimum value of parameters to extract the highest amount of steviol glycosides. The extraction was done in 3 phases. First phase was to determine the best ratio between stevia and extracting solvent, second phase determined the best extracting time and third phase was to obtain the optimum temperature. From this study, ethanol proved to be the best extracting solvent. Ethanol extraction of Rebaudioside A and stevioside in the most suitable condition (ratio 1:25, 1 hour and 40℃) produced 12.48% of stevioside and 0.57% of Rebaudioside A.